IRAN AND THE UNITED STATES AND THE NEW MIDDLE EAST SETTLEMENT - Jihad Aldeen Albadawi (European Scientific Journal, ESJ, 2015)
This study offers an analysis about the motives of the regional settlement between Iran and the United States in the Middle East. In addition, this paper examines the decline of American hegemony both globally and regionally which in turn ended the unipolar era of the international system. The study claims that due to this radical shift some regional powers have emerged. In doing so, this paper highlights the strategic changes that paved the way for such adjustments, which began at the fall of the Iraqi and Afghan regimes. As a result, this has formed the case of a regional vacuum due to the absence of an active Arab role and the failure of the US war on terrorism. Therefore, this study submits that the political landscape in the region and the decline of the US are contributing variables to highlighting Iran as a first alternative for the United States in the region. In fact, the ease in the relations between Tehran and Washington is the result of the overall changes that have swept the region. This is clear evidence for the emergence of Iran as a first and an alternative power to the United States. However, this shift and the new balance in the relations does not absolutely represent Iran as an alternative for America in the region but rather its emergence as an absolute power due to its military expansion and influential politics in the region. This paper argues that the expansion of the Islamic state’s geographical extent in Syria and Iraq as well as the failure of the international coalition led by the United States to end this expansion marked a turning point and an urgent need for US administration to accept Iran as a regional power. Indeed this shift is marked as one of the least viable solutions out of the Syrian and Iraq deadlock, and as a partner indirectly in the international war on the Islamic state. In short, the paper concluded that the United States’ influence in the Middle East region was declining slowly in the light of the expansion of Iranian influence in the region and different parts of Africa and Latin America. This has created an appropriate international atmosphere to accept Iran's presence in the Middle East as a substitute for the United States. This emergence of the new power may pave the way to a new sectarian violence.